La datation par thermoluminescence face à la production d’un nouveau type de faux - Isabelle Gerardy (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The thermoluminescence phenomenon has been use since more than 30 years to evaluate the age of certain archaeological samples. Since a couple of year, some try to pass over this test using different techniques like the artificial irradiation of recent objects or the re-use of some pieces of ancient potteries to manufacture object showing a real TL signal. Fortunately, some other analysis techniques like binocular observation or an analyse of the object style are able to distinguish true from false.